Auxiliary Fiber Art Creation Design Based on Conductive Fiber Textile Wireless Structure Sensor - Limei Ma (Hindawi Limited, 2021)
The integration of fiber materials into modern pottery creation is an attempt to explore its boundaries as a specific material and art form. Fiber materials, such as fabric and paper, are not resistant to high temperatures, and the clay attached to them can retain the surface texture, texture, and original three-dimensional form of the fiber materials intact during the kiln firing process, making up for the defects of single material molding and maintaining the visual effect of ultrathin and highly translucent works. The light source inside the work is more conducive to creating a specific artistic atmosphere. The purpose of this paper is to explore how fiber materials become the basis of ceramic works and the source of decorative expression, so that this expression and process can be systematically analyzed and interpreted in the application of ceramic art creation. Along with the rapid development of nanotechnology, electronics, and optical technology, people’s clothing fabrics have been increasing in demand in terms of function and appearance. This paper focuses on the research and development of fiber textiles from the field of science and technology and discusses the current status of fiber textiles and the possibility of combining fiber art with science and technology. In this paper, wood cellulose-multiwalled carbon nanotube/wood cellulose composite films were prepared, as well as wood cellulose films and wood cellulose/multiwalled carbon nanotube composite films. The optimal reaction time for the preparation of the films was 2 h, and the optimal reaction temperature was 70°C. Experimental results show that the dispersibility of multilayer carbon nanotubes in wood cellulose multilayer carbon nanotubes/wood cellulose composite films in wood cellulose multilayer carbon nanotubes composite films is superior. If the amount of multilayered carbon nanotubes was 3 wt%, the fracture point extension and accessibility of the wood cellulose multilayer carbon nanotubes/wood cellulose composite film are 12.2% and 106.7 MPa, respectively. It is 93.7%, respectively. 10.7% is higher than wood cellulose/multilayered carbon nanotube composite films.